Plectin is Required for Trans‐Endothelial Permeability: A Model of Plectin Dysfunction in Human Endothelial Cells After TNF‐α Treatment and Dengue Virus Infection. Issue 23 (25th November 2018) - Suttitheptumrong, Aroonroong; Rawarak, Nantapon; Reamtong, Onrapak; Boonnak, Kobporn; Pattanakitsakul, Sa‐nga
Abstract: The clinical sign of dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS) in humans is increased vascular permeability. Virus‐specific factors and host factors, including secreted cytokines and especially TNF‐α, are suggested as having roles in the pathogenesis of these conditions. Proteomic analysis with MS is performed in membrane fraction isolated from human endothelial cells (EA.hy926) upon DENV infection and TNF‐α treatment. In the 451 altered proteins that are identified, decreased plectin expression is revealed by Western blot analysis, while immunofluorescence staining (IFA) shows actin stress fiber rearrangement and decreased VE‐cadherin in treated EA.hy926 cells. In vitro vascular permeability assay was used to determine transepithelial electrical resistance (TEER) in EA.hy926 cells seeded on collagen‐coated Transwell inserts. The low level of TEER, the low expression of plectin and VE‐cadherin, and the unusual organization of actin stress fiber are found to be correlated with increased membrane permeability in DENV2 and TNF‐α‐treated EA.hy926 cells. Similar results are observed when using siRNA knockdown plectin in mock EA.hy926 cells. This study provides better understanding of the role that disruption of cytoskeleton linker protein plays in increased vascular permeability, and suggests these factors as major contributors to vascular leakage in DHF/DSS patients.